2011
DOI: 10.4103/0970-9371.83465
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology of supraclavicular lymph nodes: Our experience over a three-year period

Abstract: Aims:This study was taken up with the aim to investigate the pattern of supraclavicular lymphadenopathy among patients presenting to our tertiary care institution, evaluate the diagnostic efficacy of fine needle aspiration cytology (FNAC), and analyze the diagnostic pitfalls.Materials and Methods:A total of 215 patients were subjected to FNAC of supraclavicular lymph nodes over a three-year period (August 2006 to July 2009). Since in 18 patients as either the aspirate was inadequate or the opinion was equivoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
26
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 7 publications
10
26
1
2
Order By: Relevance
“…Squamous cell carcinoma (32.2%) followed by adenocarcinoma (22%) were the most common metastatic tumors in our study. Similar figures were also seen in a study (Mitra et al, 2011). Other studies (Khajuria et al, 2006;Izhar et al, 2007;Hirachand et al, 2009;Wilkinson et al, 2012) also found squamous cell carcinoma as the most common metatatic malignancy.…”
Section: Discussionsupporting
confidence: 77%
“…Squamous cell carcinoma (32.2%) followed by adenocarcinoma (22%) were the most common metastatic tumors in our study. Similar figures were also seen in a study (Mitra et al, 2011). Other studies (Khajuria et al, 2006;Izhar et al, 2007;Hirachand et al, 2009;Wilkinson et al, 2012) also found squamous cell carcinoma as the most common metatatic malignancy.…”
Section: Discussionsupporting
confidence: 77%
“…Squamous cell carcinoma followed by adenocarcinoma were found to be the most common tumors to metastasize to cervical lymph node in many studies [5,9,16,21] similar to our study. However, adenocarcinoma was found to be the most common metastatic tumor followed by squamous cell carcinoma in some other study [22].…”
Section: Fnac Diagnosissupporting
confidence: 79%
“…The incidence of malignancy rose steadily through the age groups to greater than 95% in patients above 60 years of age (Mitra et al, 2011). The youngest patient in our study was a 3 years old child and the oldest one was of 90 years.…”
Section: Discussionmentioning
confidence: 84%